2017
DOI: 10.1101/184879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of DNA methylation patterns in the bone and cartilage of a nonhuman primate model of osteoarthritis

Abstract: Objective: Osteoarthritis (OA) impacts humans and several other animals. Thus, the mechanisms underlying this disorder, such as specific skeletal tissue DNA methylation patterns, may be evolutionary conserved. However, associations between methylation and OA have not been readily studied in nonhuman animals. Baboons serve as important models of disease and develop OA at rates similar to those in humans. Therefore, this study investigated the associations between methylation and OA in baboons to advance the evo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Additionally, our study identified substantially more DMPs than a previous investigation of baboon OA. 17 Although this prior study used the 450K array, the total number of sites examined was similar, suggesting that increased power was primarily due to an increased sample size. The expansion of DMP findings allowed for subsequent analyses of DMRs which showed similar number trends and gene associations, further confirming the DMP results and their functional implications.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, our study identified substantially more DMPs than a previous investigation of baboon OA. 17 Although this prior study used the 450K array, the total number of sites examined was similar, suggesting that increased power was primarily due to an increased sample size. The expansion of DMP findings allowed for subsequent analyses of DMRs which showed similar number trends and gene associations, further confirming the DMP results and their functional implications.…”
Section: Discussionmentioning
confidence: 91%
“…Baboons were classified as having healthy or OA knees as previously described. 17 Briefly, each specimen was assigned an OA severity score based on macroscopic inspection of the articular surface cartilage of the distal femora: Grade 1 is unaffected, Grade 2 is mild OA (cartilage fibrillation), Grade 3 is moderate OA (cartilage lesions), and Grade 4 is advanced OA (eburnation). 12 For each sample, a cartilage scraping was obtained from the inferior aspect of the medial condyle on the right distal femur, and a trabecular bone core was obtained from a transverse plane through the center of the same condyle such that the articular surface remained preserved.…”
Section: Assessment Of Oamentioning
confidence: 99%
See 1 more Smart Citation
“…Again, position of potential mismatches was not further evaluated. The same filtering approach as proposed by Ong et al [19] was subsequently also used for a study on osteoarthritis using baboon samples which concluded that a total of 44 % of probes on the 450K BeadChip could be reliably used [20].…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-three percent of the probes designed to the human genome mapped to the bonobo genome, 72%-77% to chimpanzee, 61% to gorilla and 44% to orangutan genomes [17,18]. Studies were also performed in monkeys of the cynomolgus macaque species (Macaca fascicularis) [19], rhesus macaque (Macaca mulata, MM) [18] and baboon [20]. For example, using different selection criteria for probes yielding reliable signals, 61% of human probes were mapped and annotated to the Macaca fascicularis genome and subsequently used to study the impact of birth weight on gene methylation and expression in Macaca fascicularis [21].…”
mentioning
confidence: 99%